Evans Syndrome in a Forty-Four Years Old Male Patient: A Case Report - Rudy Afriant; Avino Mulana Fikri; Alexander Kam (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Evans syndrome (ES) is an autoimmune disease characterized by the presence of autoimmune hemolytic anemia (AIHA) and idiopathic thrombocytopenic purpura (ITP), together with unknown causes. ES disease is the least common, diagnosed in only 0.8% - 3.7% of all patients with AIHA or ITP. This study aimed to describe Evans syndrome in a 44-year-old male patient. Case presentation: A 44-year-old male patient was reported with complaints of weakness and fatigue, red spots, a history of bleeding gums, a history of bleeding from the nose, and a history of red urination. A routine blood examination revealed mild anemia, reticulocytosis, and thrombocytopenia, and the peripheral blood showed polychromatic erythrocytes. Other laboratory examinations revealed an increase in LDH. The results of a positive Comb’s test and antibody screening examination showed the impression of warm-type AIHA. The diagnosis of Evans syndrome in this patient was confirmed by the presence of AIHA and ITP, which co-occur and are primarily due to unknown causes. Conclusion: ES is a rare disorder and a diagnosis of exclusion. The diagnosis of ES was established by the presence of signs and symptoms of AIHA and ITP accompanied by a positive direct antiglobulin test with no other etiology found.